An Economy’s Emergent Properties and How Micro Agents with Inconsistent or Conflicting Interests Are Holistically Organized into Macro Entities - Forrest, Jeffrey Yi-Lin; Gong, Zaiwu; Köse, Erkan; D. Galbraith, Diane; A. Arık, Oğuzhan (Naše gospodarstvo/Our economy, 2021)
The existing literature documents that computer simulations can reveal how characteristics of micro-level individuals give rise to macro-level phenomena of systemic wholes. This paper seeks to establish such an important simulation-based observation as a theoretical result on a sound foundation. Going beyond addressing when holistic phenomena can naturally emerge from micro-level characteristics, this paper investigates how and why many macro-level entities appear to answer market calls through organically gathering micro-level agents into uniformly-oriented operational wholes, even though these agents have inconsistent or even conflicting interests. This paper develops conclusions based on results of systems science and establishes a sufficient condition under which characteristics of micro-level agents can naturally lead to the appearance of macro-level properties of a systemic whole even though the former are heterogeneous and behave in an unintended and uncoordinated manner. This paper suggests to root each theoretical result of economics on elementary facts of personal belief-value systems and expands methods of networks and computer simulations to those of systems science. It explains when macro socioeconomic phenomena emerge out of unintended and uncoordinated actions and interactions of micro economic men, and provides a more general approach for developing reliable conclusions than those observed from computer simulations. It additionally derives conditions for when macro-level economic entities appear to answer market calls and how micro-level individuals with inconsistent or even conflicting interests can be organically congregated into operational business organizations.
Keywords: Competition; emergence; holistic phenomena; market signal; system; value; yoyo model